2021
DOI: 10.1016/j.ssci.2020.105008
|View full text |Cite
|
Sign up to set email alerts
|

Creating conditions for critical trust – How an uncertainty-based risk perspective relates to dimensions and types of trust

Abstract: Highlights The paper discusses how different risk perspectives relate to types of trust. The paper highlights the importance of the scepticism dimension of trust. It provides new insights about the role of the risk assessor in this context. The analysis is based on the Social Amplification of Risk Framework. A case related to the use of a feed additive is used to illustrate the discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 60 publications
0
14
0
6
Order By: Relevance
“…The third strategy involves shifting trust over time depending on the attractiveness of communication sources (Fjaeran & Aven, 2021). This strategy has been termed reliance on vagabond trust (Renn, 2005; 2019).…”
Section: Perceptions Of Systemic Risksmentioning
confidence: 99%
“…The third strategy involves shifting trust over time depending on the attractiveness of communication sources (Fjaeran & Aven, 2021). This strategy has been termed reliance on vagabond trust (Renn, 2005; 2019).…”
Section: Perceptions Of Systemic Risksmentioning
confidence: 99%
“…Transparency is important in risk assessment and even more in RBA, which entails a higher level of complexity. Under this respect, it is worthwhile to mention the paper by Fjaeran and Aven ( 76 ): pivoting on a FEEDAP opinion as a case study, the authors highlight the importance of the “trust” and “distrust” components in the role of risk assessment. Assessors can act to improve conditions of trust by adopting an understanding of risk, stressing uncertainty and knowledge aspects when conceptualizing and characterizing risk; according to the authors, acknowledging the existence of societal “distrust” toward risk assessment and responding to it, can become a resource in order to build a “critical trust.”…”
Section: Discussionmentioning
confidence: 99%
“…Rai, Reeves, and Margolis (2016, p. 504) found that more than 50% of prospective PV customers considered the installer's opinion very important or even extremely important. Since trust presupposes a risk situation (Fjaeran & Aven, 2021; Luhmann, 1988), the study also inquired about perceived risk in the context of trust in people involved. A meta‐analysis conducted by Li et al (2020, p. 90) found a direct negative relationship between perceived risk and purchase behavior.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%